Evaluation of the diagnostic performance of PanbioTM Abbott SARS-CoV-2 rapid antigen test for the detection of COVID-19 from suspects attending ALERT center - Wondimu Ashagre; Abay Atnafu; Liya Wassie; Rea Tschopp; Dessalegn Fentahun; Gebeyehu Assefa; Teklu Wegayehu; Biniam Wondale; Andargachew Mulu; Adane Miheret; Kidist Bobosha (PLoS ONE, 2022)
Background The emergence and rapid spread of coronavirus disease 2019 (COVID-19), a potentially lethal disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is causing public health issues around the world. In resource-constrained nations, rapid Abbott SARS-CoV-2 antigen test kits are critical for addressing diagnostic gaps in health institutions and community screening. However, there is no evidence or proof of diagnostic performance in Ethiopia. The aim of this study was to compare the performance of PanbioTM Abbott SARS-CoV-2antigen rapid test kit to the gold standard, RT-PCR, in COVID-19 patients with clinical symptoms suggestive of COVID-19. Method A prospective, cross-sectional study was conducted between November 2021 and April 2022, on 120 suspected patients recruited from outpatient, emergency, and intensive care units in one of the tertiary hospitals in Ethiopia. Nasopharyngeal swabs were collected from suspected cases and were tested using the Abbott SARS-CoV-2 kit, a rapid diagnostic test (RDT) and compared to the reference standard RT-PCR. Result The sensitivity and specificity of the RDT were 74.2% and 100%, respectively. A total of 62 samples (51.6%) were RT-PCR positive. Of these, 46 were Ag-RDT positive. Sensitivity among symptomatic patients was 79.4% (95% CI 68.3–90). The Abbot RDT and RT-PCR had a Kappa value of agreement of 0.735 (p < 0.001). These values were acceptable when compared to the WHO’s suggested thresholds. Conclusion The finding from this study support the use of the Abbot RDT as a diagnostic tool in COVID-19 suspects, mainly in those with higher viral loads.